Physicochemical Characterisation of White Pepper : A Comparative Study Between Traditional Sun Drying and Convective Rotary Drum Drying Methods - Ana Sakura, Zainal Abidin; Mohamad Syafiq Iylia, Jamadi; Sinin, Hamdan; Mohammad Omar, Abdullah; Gloria Elaine, John; Annisa, Jamali; Rasli, Muslimen; Zehnder Jarroop, Augustine Mercer (Universiti Putra Malaysia Press, 2024)
Drying is a crucial process in preserving the physicochemical qualities of white pepper. This study investigates the impact of two drying processes, namely traditional sun drying (TSD) and rotary drum drying (RDD), on the quality of white pepper. TSD requires three consecutive sunny days for drying, whereas RDD achieves the target moisture content of 12% within a rapid drying time of 120 min. The research employs thermo-gravimetric analysis (TGA), Fourier transform infrared (FTIR) spectroscopy analysis, and scanning electron microscopy (SEM) to analyse the dimensions, thermo-physical profiles, chemical constituents, and microstructure of the pepper samples. RDD, with a drying temperature of 55°C and centrifugation force of 129.7 × g, ensures fast and uniform drying while preserving the physicochemical qualities of white pepper. In terms of physical characteristics, RDD results in larger dried pepper dimensions, measuring 4.56 mm on average, compared to TSD, which measures 4.35 mm. SEM observations reveal varying pore sizes and cracks in both drying methods. Additionally quality validation conducted by the Malaysian Pepper Board demonstrates that RDD exhibits superior quality compared to TSD. The RDD samples show moisture content, piperine, volatile, and ash percentages of11.83, 8.18, 2.53, and 0.82, respectively, while the TSD samples show 10.37, 7.16, 2.43, and 0.74. All samples complied with Standard Malaysian White Pepper No. 1 and International Pepper Community Grade 1. Future studies should focus on enhancing different drying methods to achieve efficient white pepper drying while preserving its quality.